2022
DOI: 10.1115/1.4053350
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Geometry of Solid Wall on the Collapse of a Cavitation Bubble

Abstract: The objective of this paper is to reveal the influence of different surface geometric conditions on the dynamic behavior characteristics of a laser-induced bubble collapse. A high-speed camera system was used to record the oscillation process of the laser-induced bubble on plane solid walls with different roughness and a wall containing reentrant cavities full of water or gas. The focus is on the quantitative analysis of the morphological characteristics of the cavitation bubble near the solid wall under diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Recently, Gonzales-Avila et al [33] released that the air trapped inside cavities could repel the bubbles away from the boundary surface, therefore preventing cavitation damage. Similarly, Sun et al [34] also found that the solid surface with several cavities containing gas enabled the direction of motion of the jet produced by the bubble collapsing to flow away from the wall. Subsequently, their newest work [35] found that the solid wall with a gas entrapping hole also changed the migration direction of the cavitation bubble.…”
Section: Introductionmentioning
confidence: 85%
“…Recently, Gonzales-Avila et al [33] released that the air trapped inside cavities could repel the bubbles away from the boundary surface, therefore preventing cavitation damage. Similarly, Sun et al [34] also found that the solid surface with several cavities containing gas enabled the direction of motion of the jet produced by the bubble collapsing to flow away from the wall. Subsequently, their newest work [35] found that the solid wall with a gas entrapping hole also changed the migration direction of the cavitation bubble.…”
Section: Introductionmentioning
confidence: 85%
“…(2020) and Sun et al. (2022 a ), who considered surfaces with a pattern of gas-entrapping holes. In all these cases, bubbles were found to translate away from the boundary, acting analogously to a typical free surface.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sun et al (2022b) investigated bubble collapse near a rigid surface with a gas-entrapping hole. This concept was also investigated by Gonzalez-Avila et al (2020) and Sun et al (2022a), who considered surfaces with a pattern of gas-entrapping holes. In all these cases, bubbles were found to translate away from the boundary, acting analogously to a typical free surface.…”
Section: Introductionmentioning
confidence: 99%
“…Lots of scholars [10][11][12][13][14][15] then studied influences of the dimensionless parameter  on bubble dynamics, including the bubble collapse time, the micro-jet and contra-jet phenomena, and features of the pressure and velocity distribution with different  .…”
Section: Introductionmentioning
confidence: 99%